2022
DOI: 10.11646/phytotaxa.542.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Tricholoma colposii (Tricholomataceae, Basidiomycota), a new edible species of matsutake fungi from Eastern Mexico with economic and biocultural importance

Abstract: Matsutake fungi include a complex of edible mushrooms highly prized worldwide, particularly in Japan where they are considered one of the most luxurious ingredients. These species establish ectomycorrhizal symbioses with angiosperms and gymnosperms in the Northern Hemisphere and in North America only three species are currently known. In the present contribution a fourth species of this geographical area is described, Tricholoma colposii sp. nov. is described from Veracruz state, in eastern Mexico based on mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Important information on the macroscopic variation of the basidiomes is also provided by the images of the specimens found in Arizona by Clements andFulton (2022), andFrank (2022), where the lamellae and ornamentation of pileus and stipe and their colors are shown in detail. Based on our molecular analyses, we observe a discrepancy with the results on T. colposii by Ayala-Vásquez et al (2022). In the latter research it was reported that after a BLAST analysis, they obtained a similarity percentage of 94% between a single sequence (of four) of ITS (668 bp) of T. colposii with T. mesoamericanum.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…Important information on the macroscopic variation of the basidiomes is also provided by the images of the specimens found in Arizona by Clements andFulton (2022), andFrank (2022), where the lamellae and ornamentation of pileus and stipe and their colors are shown in detail. Based on our molecular analyses, we observe a discrepancy with the results on T. colposii by Ayala-Vásquez et al (2022). In the latter research it was reported that after a BLAST analysis, they obtained a similarity percentage of 94% between a single sequence (of four) of ITS (668 bp) of T. colposii with T. mesoamericanum.…”
Section: Resultscontrasting
confidence: 87%
“…In the latter research it was reported that after a BLAST analysis, they obtained a similarity percentage of 94% between a single sequence (of four) of ITS (668 bp) of T. colposii with T. mesoamericanum. However, our BLAST analysis showed a rank of similarity percentage of 99.66-99.82% among the four sequences of T. colposii by Ayala-Vásquez et al (2022) with the type of T. mesoamericanum, and 100% similarity percentage with one sequence identified as T. matsutake from Mexico (AB036891). Furthermore, in the phylogeny obtained in such research, T. colposii appears in a well-supported clade, on a relatively long branch, as sister to T. mesoamericanum, which is not consistent with the great similarity among the sequences, observed through BLAST analysis.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The sequences generated in this study, and sequences retrieved from GenBank, were used for molecular phylogenetic analysis following Cai et al (2018) and Liang et al (2018). For rooting purpose, Tricholoma bakamatsutake Hongo (AF204807) was used as the outgroup taxon (Ayala-Vasquez et al 2022). The consensus sequences were subjected to BLAST and compared with available GenBank sequences.…”
Section: Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%
“…However, only a limited number of species were included in these studies. Although more than 30 species have been described based on phylogenetic analyses in recent years ( Christensen & Heilmann-Clausen 2009 , Hosen et al 2016 , Heilmann-Clausen et al 2017 , Trudell et al 2017 , Yang et al 2017 , Ovrebo & Hughes 2018 , Reschke et al 2018 , Ovrebo et al 2019 , Xu et al 2020 , Trudell & Parker 2021 , Ushijimaa et al 2021 , Ayala-Vásquez et al 2022 , Cui et al 2022 , Ding et al 2022 ), the infrageneric classification of the genus remains unsettled.…”
Section: Introductionmentioning
confidence: 99%